The participation of staff in decision making and its impact on performance A case study of Saudi Telecom company (STC) 2016 – 2012 - Hafez, Hassan Mohamed Hassan (Journal of Economic, Administrative and Legal Sciences, 2018)
The research treated the participation of staff members in decision making and its impacts on performance, taking Saudi Telecom company (STC) as a case study, The aim of the research is to identify the administrative method followed in the decision-making management and the interest of leaders in business enterprises with the participation of subordinates in the decision-making management, The research was based on the following hypotheses: There is statistically significant evidence between employee’s participation in administrative decision making and their motivation to carry out their duties in Saudi Telecom company. There is statistically significant evidence between employee’s participation in administrative decision making and developing both communication with their superiors and spirit of united team in Saudi Telecom Company. There is statistically significant evidence between employee’s participation in administrative decision making and the increase of productivity of their jobs in Saudi Telecom Company. The descriptive method and the historical narrative were used in preparing the study. The researcher treated the data obtained from the field study statistically using the (SPSS) program. The research reached many results, the most important of which is to prove the validity of the above hypotheses. The research also has several recommendations that can be of benefit to decision makers in the private and public sectors: The necessity of adopting decentralization in administrative decision making. Encouraging the subordinates to participate in administrative decisions. Holding training courses for the subordinates in the field of decision making. Overcoming selfishness, self-esteem and controlling of customs, traditions and tribalism when making administrative decisions.